Y-chromosome loss is frequent in male renal tumors - Büscheck, Franziska (Ann Transl Med, 2021)
BACKGROUND: Loss of the Y-chromosome is a common event in different tumor types but its prevalence and clinical relevance in renal cell tumors is still not understood. METHODS: It was the aim of this study to estimate the frequency and clinical relevance of Y-loss in kidney neoplasms. A cohort of 1,252 male renal tumors was analyzed in a tissue microarray format by fluorescence in-situ hybridization (FISH). RESULTS: Y-loss was found in 47% of tumors. The frequency of this alteration varied markedly between kidney tumor subtypes. Y-loss was most prevalent in papillary renal cell carcinoma (RCC) (77%) followed by chromophobe RCC (60%), oncocytoma (51%), clear cell RCC (39%) and clear cell (tubulo)papillary RCC (19%). Y-loss was linked to higher patient age and smaller tumor size at diagnosis. Mean age (95% CI) was 65 (64–66) years in patients with Y-loss in their tumor compared to 60 (58–61) years in patients without Y-loss (P<0.0001). Significant correlations between Y-loss and tumor phenotype were found only for papillary carcinomas (P=0.002), especially for type 1 (P=0.03). CONCLUSIONS: Y-loss is present in different histologic subtypes of renal neoplasm. The highest frequency is in papillary RCC, where it may represent a potentially relevant prognostic biomarker suggesting favorable disease outcome.